2021
DOI: 10.3390/cells10061310
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated Proteome Profiling Identifies a Fucosylated, Non-Ribosomal, Stress-Responsive Species of Ribosomal Protein S3

Abstract: Alterations in genes encoding for proteins that control fucosylation are known to play causative roles in several developmental disorders, such as Dowling-Degos disease 2 and congenital disorder of glycosylation type IIc (CDGIIc). Recent studies have provided evidence that changes in fucosylation can contribute to the development and progression of several different types of cancers. It is therefore important to gain a detailed understanding of how fucosylation is altered in disease states so that intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…5c ). Lectin-mediated PLA (LPLA, a method developed in our laboratory 15 , 16 that allows for the visualization of specific fucosylated proteins) also confirmed that knockdown or overexpression of FUT4 resulted in reduced or increased, respectively, cellular levels of fucosylated L1CAM (fuco-L1CAM) (Fig. 5c and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…5c ). Lectin-mediated PLA (LPLA, a method developed in our laboratory 15 , 16 that allows for the visualization of specific fucosylated proteins) also confirmed that knockdown or overexpression of FUT4 resulted in reduced or increased, respectively, cellular levels of fucosylated L1CAM (fuco-L1CAM) (Fig. 5c and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Indeed, in cancer, aberrant levels of fucosylated proteins have been reported 10 , but their specific mechanistic roles in cancer pathogenesis are unclear. Aberrant structural subtypes of fucosylation ( e.g ., core fucosylation) have been reported in melanoma 12 , 13 , and we previously discovered that global fucosylation is deregulated during melanoma progression, impacting motility and RNA processing of melanoma cells 14 , 15 and altering crucial tumor:immunological interactions that are required for anti-tumor immunity 16 . Intriguingly, our recent work uncovered that global tumoral fucosylation is significantly lower in male compared to female melanoma patients, suggesting sex-associated divergence in fucosylation-regulated melanoma biology 16 .…”
Section: Introductionmentioning
confidence: 92%
“…Proteins related to the damage response deserve attention as they may be related to radio- and/or chemoresistance or drug sensitivity, thus encompassing potential drug targets through the inhibition of FucT-8 activity (cluster c, Figure ). In this sense, it has recently been described that deregulated fucosylation can affect many intracellular proteins, including the ribosomal protein S3, which participates in nuclear DNA repair . Indeed, the fucosylation and sialylation inhibitor pictilisib affected the DNA repair capacity of lung cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it has recently been described that deregulated fucosylation can affect many intracellular proteins, including the ribosomal protein S3, which participates in nuclear DNA repair. 113 Indeed, the fucosylation and sialylation inhibitor pictilisib affected the DNA repair capacity of lung cancer cells. 114 The histone H2AFJ (cluster e) is usually expressed in luminal epithelial cells, although its role is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that fucose binding lectin and many other intracellular proteins undergoes post-translation fucosylation. The ribosomal protein S3 (RPS3) is fucosylated in human cancer cells and normal mouse tissue [ 199 ].…”
Section: Rrna and Ribosomal Protein Modification In Cancer Diseasesmentioning
confidence: 99%